PREVALENCE AND CLINICAL PROFILES OF PAEDIATRIC SEIZURES IN EMERGENCY SETTING - Bushra Memon; Ayesha Khatoon; Amanullah Lail; Faiza; Ainey Razzak; Mushtaque Ali Shah (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Seizures are characterized by unusual, excessive electrical activity in the brain's neurons, which can lead to changes in behaviour, consciousness, or physical movements. These episodes are common in neurology and can result from various conditions, including epilepsy, infections, brain tumors, head injuries, and metabolic disturbances.Objectives: The objective of this study was to identify and report the different types of seizures presenting in the emergency department, based on their clinical features, duration, and underlying causes.Study design: A cross-sectional studyPlace and Duration: This study was conducted in Dr Ruth K.M Pfau, Civil Hospital Karachi from March 2023 to March 2024Methodology: The study included pediatric patients, and data was gathered on their medical histories, clinical presentations, and demographic details. The questionnaire included sections on demographic information (age, gender, and residential area), medical history, clinical presentation, type of seizure, duration of seizure, and potential underlying causes. Clinical presentations were categorized based on the initial assessment by emergency department physicians and corroboratedwith subsequent evaluations by neurologistsResults: Among the 120 cases recorded, febrile seizures were the most common, followed by seizures due to encephalitis and hypoxic-ischemic encephalopathy. Seizures due to epilepsy, metabolic disorders, electrolyte imbalances, structural brain abnormalities, and other etiologies were less frequent. Recurrence of seizures was noted in less than half of the patients. All necessary interventions were implemented to manage the seizures effectively, aiming to prevent complications and ensure the best possible outcomes for the children.Conclusion: In the pediatric population under study, febrile seizures were the most frequently observed type of seizure.